Work-related stress assessment in an emergency department in French Guiana. (13th May 2021) - Pujo, Jean Marc; Kraiem, Hajer; Daniel, Pierre; Omri, Majdi; Fremery, Alexis; Rémi, Mutricy; Madani, Galleze; Tsafehy, Mosa; Resiere, Dabor; Hommel, Didier; Kallel, Hatem
Abstract : Background: In emergency departments (EDs), the staff continually face stressful situations requiring staff to adopt various coping strategies. Aims: The study aimed to assess work-related stress in ED during the COVID-19 outbreak. Method: The study was a monocentric investigation based on a questionnaire survey that elicits general information and uses the Karasek model to analyse the data. Findings: A total of 117 forms were collected for analysis. The score for decision latitude (or autonomy and skills at work) was 70 (IQR: 64–74) and the score for psychological demand was 25 (IQR: 23-27). The score for social support by the management team was 11 (IQR: 9–12) and the score for social support by colleagues 12 (IQR: 10–12). Of the total number of respondents, job strain was assessed as affecting 24.8%. Conclusion: The study shows high levels of stress among the ED workforce. The findings indicate that it is imperative to develop simple management tools that are capable of measuring the internal causes of stress in order to develop an adapted wellness programme in ED.